Pengaruh Profitabilitas, Risiko Keuangan, Nilai Perusahaan, Kepemilikan Manajerial, dan Dividend Payout Ratio Terhadap Praktik Perataan Laba (Studi Empiris Pada Perusahaan Real Estate dan Properti yang Terdaftar Di Bursa Efek Indonesia Tahun 2011-2013) - Adi, Prima Sapta; Nasir, Azwir; -, Rusli (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This study aims to demonstrate the influence of profitability, financial risk, firm value, managerial ownership, and dividend payout ratio toward income smoothing practice done by management. The population in this study is all real estate and property company listed on Indonesian Stock Exchange (IDX). Samples were decided by using purposive sampling method. Samples in this study choose based on several criteria and as much as 35 (thirty five) companies were selected. The methodology used in this is multiple regressions analysis. The results of this study stated that financial risk (LEV) has significant effect to the income smoothing practice of real estate and Property Company listed on Indonesian Stock Exchange year 2011-2013. While the ROA, PBV, MOWN, and DPR have no significant effect to the income smoothing practice of real estate and Property Company listed on Indonesian Stock Exchange in 2011-2013. Coefficient of determination obtained amount to 0,167 or 16,7%. It indicates that income smoothing practices in real estate and Property Company are described by 16,7% by ROA, LEV, PBV, MOWN, and DPR. The remaining of 83,3% are influenced by other factor which were not examined in this study.Keywords: Profitability (ROA), Financial Risk (LEV), Firm Value (PBV), Managerial Ownership (MOWN), Dividend Payout Ratio (DPR), Income Smoothing Practice.